2006
DOI: 10.1590/s1516-35982006000500003
|View full text |Cite
|
Sign up to set email alerts
|

Histologia da pele da carpa prateada (Hypophtalmichthys molitrix) e testes de resistência do couro

Abstract: RESUMO -Este estudo foi realizado com os objetivos de analisar a histologia da pele e avaliar a influência da técnica de curtimento e da posição da retirada do corpo-de-prova sobre a qualidade da pele de carpa prateada (Hypophtalmichthys molitrix). Vinte e três peixes foram insensibilizados para retirada das peles para curtimento. Amostras referentes a três peixes foram fixadas em formol 10%. Após a inclusão em parafina, foram cortadas com aproximadamente 5 mm de espessura e coradas pela técnica de hematoxil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
2
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 1 publication
1
2
0
2
Order By: Relevance
“…Gomes (2008) studied the histological characteristics of hide of the acoupa weakfish (C. acoupa) and smooth weakfish (C. leiarchus), and confirmed that both have the same arrangement of birefringent collagen fibers, forming thick and twisted fibers, arranged both longitudinally and transversally. This arrangement of collagen fibers in the acoupa weakfish is similar to the silver-plated carp mentioned by Souza et al (2006). The resistance test, however, revealed that the acoupa weakfish hide was more resistant than that of the silver-plated carp tanned with plant tannin or chromium.…”
Section: Resultssupporting
confidence: 72%
See 1 more Smart Citation
“…Gomes (2008) studied the histological characteristics of hide of the acoupa weakfish (C. acoupa) and smooth weakfish (C. leiarchus), and confirmed that both have the same arrangement of birefringent collagen fibers, forming thick and twisted fibers, arranged both longitudinally and transversally. This arrangement of collagen fibers in the acoupa weakfish is similar to the silver-plated carp mentioned by Souza et al (2006). The resistance test, however, revealed that the acoupa weakfish hide was more resistant than that of the silver-plated carp tanned with plant tannin or chromium.…”
Section: Resultssupporting
confidence: 72%
“…Therefore, further studies comparing hides greased with andiroba oil and other types of oils are required to assess whether there is any effect of these oils on the physico-mechanical properties. Souza et al (2006) performed histological analyses and resistance test on the hide of the silverplated carp (Hypophtalmichthys molitrix) tanned with plant tannin and chromium and found that the hide of the silver-plated carp is composed of a thick dermis and with collagen fibers parallel and transverse to the hide surface, which according to the authors, confers resistance to the hide. The hide tanned with chromium had a greater resistance to traction at 16.96 N mm -2 , tensile strength of 104.74 N and stretching of 51.49% compared with those tanned using tannins: 9.12 N mm -2 , 58.81 N, and 17.48%, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Para Junqueira et al (1983), essas camadas são classificadas em: derme frouxa (delgada superficial) e outra compacta (profunda e espessa), representadas na figura 5. Souza (2006) em análise com a pele da carpa prateada também observou que na camada mais profunda, as fibras colágenas são mais finas e próximas, com pouco espaço interfibrilar à medida que se aproximam da hipoderme. Ainda, Franco et al (2015) afirmam que as fibras de colágeno podem influenciar na espessura do couro.…”
Section: Resultados E Discusãounclassified
“…Também Souza (2004) cita que a disposição, orientação e constituição das fibras colágenas influenciam na resistência do couro. Souza (2006) relata que pesquisadores podem aprimorar as técnicas para curtimento de couros de peixes com cromo ou taninos (vegetal, sintéticos ou ambos) como agentes curtentes, para tornar fonte de renda a mais com o reaproveitamento dos resíduos de pescados. As peles antes desperdiçadas, agora podem ser aproveitadas na indústria de confecções, como vestuários, calçados e artefatos.…”
Section: Introductionunclassified
“…Abraham et al, 2001;Domingues and Hayashi, 1998;Grizzle and Thiyagarajah, 1987;Fujimoto et al, 2008;Koumans and Sire, 1996;;Langer et al, 2004;Lyng et al, 2004;Mittal and Whitear, 1979;Moss, 1972;Nolan et al, 2002;Sire and Akimenko, 2004;Sire et al, 1997;Souza and Santos, 1997;Souza et al, 2003;Souza et al, 2006;Yuan and Campana, 1998;Waterman, 2005). However, the descriptive work dates from twenty or thirty years ago and bears very little photographic record.…”
Section: Introductionmentioning
confidence: 99%